Improvement in management reporting of IS09000 companies and its relationship with performance - Isa, C.R.; Ying, W.; Oon Nee, E.Y. (2010)
In the last two decades, there have been an increasing number of organizations obtaining accreditation from the International Organization for Standardization (ISO). ISO 9000 was created to assist organizations worldwide in their pursuit for quality management practices.There have been numerous debates on whether the benefits of ISO certification outweigh its costs. A review of past literature on ISO 9000 reveals vague, mixed and inconclusive results of the relationship between ISO certification and performance, both financial and non-financial. This study investigates the relationship between improvement in management reporting and business performance among ISO 9000 companies in Malaysia. A personally administered questionnaire survey was conducted to collect data from randomly selected ISO certified firms listed in the SIRIM Directory of Certified Products and Companies. The survey results revealed significant relationships between management reporting and performance, consistent with the predictions about the hypothesized relationships between management reporting and performance. The results suggest that improved management reporting in ISO companies is significantly related to overall performance as well as to each component of performance, namely product quality, customer satisfaction and profitability.